Analysing 'big picture' policy reform mechanisms: the Australian health service safety and quality accreditation scheme. (4th November 2014) - Greenfield, David; Hinchcliff, Reece; Banks, Margaret; Mumford, Virginia; Hogden, Anne; Debono, Deborah; Pawsey, Marjorie; Westbrook, Johanna; Braithwaite, Jeffrey
Abstract: Background: Agencies promoting national health‐care accreditation reform to improve the quality of care and safety of patients are largely working without specific blueprints that can increase the likelihood of success. Objective: This study investigated the development and implementation of the Australian Health Service Safety and Quality Accreditation Scheme and National Safety and Quality Health Service Standards (the Scheme), their expected benefits, and challenges and facilitators to implementation. Methods: A multimethod study was conducted using document analysis, observation and interviews. Data sources were eight government reports, 25 h of observation and 34 interviews with 197 diverse stakeholders. Results: Development of the Scheme was achieved through extensive consultation conducted over a prolonged period, that is, from 2000 onwards. Participants, prior to implementation, believed the Scheme would produce benefits at multiple levels of the health system. The Scheme offered a national framework to promote patient‐centred care, allowing organizations to engage and coordinate professionals' quality improvement activities. Significant challenges are apparent, including developing and maintaining stakeholder understanding of the Scheme's requirements. Risks must also be addressed. The standardized application of, and reliable assessment against, the standards must be achieved to maintain credibility with the Scheme. Government employment of effective stakeholder engagement strategies, such as structured consultation processes, was viewed as necessary for successful, sustainable implementation. Conclusion: The Australian experience demonstrates that national accreditation reform can engender widespread stakeholder support, but implementation challenges must be overcome. In particular, the fundamental role of continued stakeholder engagement increases the likelihood that such reforms are taken up and spread across health systems.